Analisis Dampak Pencemaran Udara terhadap Kesehatan Pernapasan Masyarakat Perkotaan - Maharani, Sheila (Gema Cendekia Institute, 2025)
Air pollution has become a critical environmental issue, particularly in densely populated urban areas, where high levels of emissions from transportation, industry, and household activities contribute to deteriorating air quality. This study aims to analyze the impact of air pollution on the respiratory health of urban populations. By combining quantitative data from air quality monitoring stations with qualitative data obtained through health surveys and medical records, this research identifies significant correlations between exposure to pollutants—such as PM2.5, NO₂, and SO₂—and the incidence of respiratory diseases including asthma, bronchitis, and chronic obstructive pulmonary disease (COPD). The findings indicate that prolonged exposure to poor air quality substantially increases the risk of respiratory issues, especially among vulnerable groups such as children, the elderly, and individuals with pre-existing conditions. This study highlights the urgent need for effective environmental policies and public health interventions to mitigate the negative health impacts of urban air pollution